2007
DOI: 10.1007/s10764-006-9096-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Plant and Soil Chemistry on Food Selection, Ranging Patterns, and Biomass of Colobus guereza in Kakamega Forest, Kenya

Abstract: Nutritional factors are among the most important influences on primate food choice. We examined the influence of macronutrients, minerals, and secondary compounds on leaf choices by members of a foli-frugivorous population of eastern black-and-white colobus-or guerezas (Colobus guereza)-inhabiting the Kakamega Forest, Kenya. Macronutrients exerted a complex influence on guereza leaf choice at Kakamega. At a broad level, protein content was the primary factor determining whether or not guerezas consumed specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
67
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 78 publications
(84 reference statements)
3
67
0
Order By: Relevance
“…For example, Waterman et al (1988) proposed that the weighted contributions of the protein-to-fiber ratios of the mature leaves of the most abundant trees in a particular area could predict the biomass of folivorous colobines. This index of dietary quality has been applied successfully to predict the biomass of folivorous monkeys at local Ganzhorn 2002) and regional (Waterman et al 1988;Oates et al 1990;Ganzhorn 1995;Chapman et al 2004;Fashing et al 2007) scales. Davies (1994) suggested that the year-round availability of digestible mature leaves with high protein-to-fiber ratios, which are used by colobus species when other, more preferred foods are unavailable, serves to limit the size of colobine populations (i.e., high protein-to-fiber mature leaves are important fallback foods).…”
Section: Previous Studies On Primate Abundancementioning
confidence: 99%
“…For example, Waterman et al (1988) proposed that the weighted contributions of the protein-to-fiber ratios of the mature leaves of the most abundant trees in a particular area could predict the biomass of folivorous colobines. This index of dietary quality has been applied successfully to predict the biomass of folivorous monkeys at local Ganzhorn 2002) and regional (Waterman et al 1988;Oates et al 1990;Ganzhorn 1995;Chapman et al 2004;Fashing et al 2007) scales. Davies (1994) suggested that the year-round availability of digestible mature leaves with high protein-to-fiber ratios, which are used by colobus species when other, more preferred foods are unavailable, serves to limit the size of colobine populations (i.e., high protein-to-fiber mature leaves are important fallback foods).…”
Section: Previous Studies On Primate Abundancementioning
confidence: 99%
“…These citations follow other second papers in the IJP sharing a dataset with previous papers (e.g. Davies et al 1999;Li and Rogers 2006;Fashing et al 2007). During the review, I revised the paragraph (content) linking the 2 papers as suggested by Dr. Setchell, and we both referred to the 2007 paper.…”
mentioning
confidence: 86%
“…Marked interspecific variability is found between primates with respect to choice or avoidance of plant foods high in tannins and phenolics [Milton, 1979;Oates et al, 1980;Wrangham and Waterman, 1981;Glander, 1982;Oates, 1988; Gould /Constabel /Mellway /Rambeloarivony 1996;Bocian, 1997;Remis et al, 2001;Chapman and Chapman, 2002;Fashing et al, 2007]; however, most primate species include at least some plant foods in their diet and therefore regularly ingest tannins and phenolics to a certain degree.…”
Section: Introductionmentioning
confidence: 99%
“…Plants containing tannins are astringent and unpalatable, an adaptation to deter consumption by herbivores [Janzen, 1974;McKey et al, 1978;Chapman and Chapman, 2002]. Some primate species or populations actively avoid potential food items containing moderate to high amounts of tannins, for example red colobus and black-and-white colobus at Kibale, Uganda [Oates, et al, 1977;Chapman and Chapman, 2002], and at Kakamega Forest, Kenya [Fashing et al, 2007], lesser bamboo lemurs and brown mouse lemurs [Ganzhorn, 1989] and vervets [Wrangham and Waterman, 1981], while others do not, e.g. howler monkeys [Milton, 1979;Milton et al, 1980], Verreaux's sifaka [Carrai et al, 2003;Yamashita, 2008], diademed sifaka and indri Mowry, 2003, 2006], greater dwarf lemurs and brown lemurs [Ganzhorn, 1989] and lowland gorillas [Remis and Kerr, 2002].…”
Section: Introductionmentioning
confidence: 99%